Gene-environment interactions in Autism Spectrum Disorder (ASD) - Xavier Santos, João (2017)
Autism Spectrum Disorder – Background: Phenotypically heterogeneous neurodevelopmental disorder, with a global prevalence rate of 1% , characterized by deficits in social communication and interaction and stereotyped and repetitive behaviours. - Genetic factors, namely rare copy number variants (CNVs), are responsible for a considerable fraction of ASD cases . - The recent heritability estimates of approximately 50% suggest a role of nongenetic factors in ASD etiology. - Pre-, peri- and post-natal exposure to toxic environmental factors has been implicated in the development of the disorder[5][6] . - ASD is most probably explained by a polygenic and multifactorial mechanism that involves genetic, environmental and epigenetic interactions. Objectives: 1. To identify specific exposure patterns to environmental toxicants, potentially involved in ASD etiology, in a dataset of Portuguese children diagnosed with the disorder, aged 7-9 years old; 2. To identify variants of ASD-candidate genes interacting with environmental factors 3. To build a global mathematical model that integrates genetic and environmental biomarkers with clinical data for risk assessment in ASD.